Solución pacífica de conflictos - Calapaqui Pallo, Paulina Maribel (2017)
The project entitled is “Peaceful Solving of Conflicts” focuses on the problem that are present today in all areas, such us: political, social and cultural. The main theme of this project is involved to the educational theme, since it is lived day by day in the school of Basic General Education "Gustavo Iturralde" disagreements among students, teachers, parents and authorities so it causes an unfavorable environment in the teaching and learning process. For this project, the objectives that are developed benefit the institution with the purpose to know the influence of the Peaceful Solving of Conflicts in order to have a harmonious environment among the members of the educational community. We also researched theoretical foundation that allows to know the subject in depth, to design methodological processes that collaborate with the solution of this problem and finally to apply research instruments in the involved entities with the purpose in order to collect veridical information....